Myopathy, lactic acidosis and sideroblastic anemia 1 (MLASA1): A 25-year follow-up - Woods, Jeremy (Mol Genet Metab Rep, 2019)
Mitochondrial myopathy, lactic acidosis and sideroblastic anemia 1 (MLASA1) is a rare disease caused by biallelic pathogenic variants in the PUS1 gene. There are eleven MLASA1 patients reported worldwide with the majority of the patients originating from the Shiraz region of Iran. The rarity of this disease poses challenges to counseling patients due to a lack of natural history data. This report reviews what is known regarding MLASA1 and describes two brothers with MLASA1 who were cared for over the course of 10 years at the University of California Los Angeles. The brothers suffered from chronic anemia, transfusion dependency and muscle wasting that lead to respiratory insufficiency and death in one of the brothers.